2017
DOI: 10.1038/s41598-017-03222-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in novel haematological parameters following thermal injury: A prospective observational cohort study

Abstract: The mortality caused by sepsis is high following thermal injury. Diagnosis is difficult due to the ongoing systemic inflammatory response. Previous studies suggest that cellular parameters may show promise as diagnostic markers of sepsis. The aim of this study was to evaluate the effect of thermal injury on novel haematological parameters and to study their association with clinical outcomes. Haematological analysis was performed using a Sysmex XN-1000 analyser on blood samples acquired on the day of the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In the present study, plasma MDA levels were significantly increased, thus demonstrating severe lipid peroxidation following considerable burn injury, a finding consistent with other studies (54,55). The pathophysiological alterations are most likely a consequence of ischemia/reperfusion injury and polymorphonuclear cell activation both locally and in the systemic circulation resulting in free-radical overgeneration (56,4). On the other hand, the depletion of plasma glutathione and antioxidant enzymes has been shown as a cause for the manifestations of the systemic oxidative response and the aggravation of the pathological processes in thermal trauma (57).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, plasma MDA levels were significantly increased, thus demonstrating severe lipid peroxidation following considerable burn injury, a finding consistent with other studies (54,55). The pathophysiological alterations are most likely a consequence of ischemia/reperfusion injury and polymorphonuclear cell activation both locally and in the systemic circulation resulting in free-radical overgeneration (56,4). On the other hand, the depletion of plasma glutathione and antioxidant enzymes has been shown as a cause for the manifestations of the systemic oxidative response and the aggravation of the pathological processes in thermal trauma (57).…”
Section: Discussionsupporting
confidence: 92%
“…Their count in systemic circulation also increases. (4) Tumor necrosis factor-α (TNF-α) is a cytokine presenting with a variety of biological effects (11) and…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental results showed that MDW has a higher diagnostic performance than white cell count (WBC) in the diagnosis of sepsis. Ayres, Cornet, and Dinsdale also found that changes in the cellular complexity and nucleic acid content of neutrophils can reflect the infection status of the body, assisting the early diagnosis of sepsis (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 97%
“…sGPVI discriminatory power may further increase if used in combination with other strong sepsis predictive markers such as cell-free DNA and immature granulocytes. 37,38 This inflammatory trauma cohort presumably contained an abundance of healthy people who were essentially well and unencumbered before receiving their injury. Measurement of sGPVI on day 1 could potentially enable clinicians to stratify patients based on sepsis risk and aid clinical management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-nine patients with injury afflicting up to 95% total body surface area (TBSA) were recruited to the Scientific Investigation of the Biological Pathways Following Thermal Injury Study (SIFTI: REC-12/EM/0432) at the Queen Elizabeth Hospital, Birmingham, United Kingdom. 37,38 Citrated blood was collected at intervals after injury (day [D] 1, D3, D7, D14, D21, and D28 and month 2, 3, 6, and 12 postinjury). Sepsis diagnosis was made when more than 3 American Burn Association criteria 39 were met, plus positive bacterial culture and/or evidence of antibiotic response.…”
Section: Blood Collectionmentioning
confidence: 99%